Marketization, Social Protection, Emancipation: Toward a Neo-Polanyian Conception of Capitalist Crisis - Fraser, Nancy (Business as Usual: The Roots of the Global Financial Meltdown, 2011)
BOOK ABSTRACT: Situates the current crisis in the historical trajectory of the capitalist world-system, showing how the crisis was made possible not only by neoliberal financial reforms but by a massive turn away from manufacturing things of value towards seeking profit from financial exchange and credit. Much more basic than the result of a few financial traders cheating the system, this is a potential historical turning point. In original essays, the contributors establish why the system was ripe for crisis of the past, and yet why this meltdown was different. The volume concludes by asking whether as deep as the crisis is, it may contain seeds of a new global economy, what role the US will play, and whether China or other countries will rise to global leadership. Contributors include: Giovanni Arrighi, Gopal Balakrishnan, Manuel Castells, Daniel Chirot, Fernando Coronil, Nancy Fraser, James K. Galbraith, David Harvey, Caglar Keyder, Beverly J. Silver, and Immanuel Wallerstein. The three volumes can purchased individually or as a set. Business as Usual is the first part of a trilogy comprised of the first three books in the Possible Future series. Volume 1: Business as UsualVolume 2: The Deepening CrisisVolume 3: Aftermath The three volumes are linked by a common introduction and can be purchased individually or as a set.
Philosophy; Political Science
Keywords: capitalism; emancipation; feminism; gender; welfare state